Behaviour of lightweight concrete slabs acting compositely with steel I-sections. (15th October 2016) - Lasheen, Mahmoud; Shaat, Amr; Khalil, Ayman
Highlights: Using lightweight concrete slab instead of normal weight concrete has slight effects on both the load capacity and ductility of composite beams. The effective concrete slab width-to-span ratio is found to be greatly affected by the slenderness ratio of the steel beam. As the slenderness ratio of the beam increases the effective width-to-span decreases. The effective width is not constant during the beam loading. The effective width for strength design (at ultimate) is wider than that at service loads. Abstract: An experimental study is carried out in this paper to investigate the validity of using lightweight concrete slabs in steel-concrete composite beams and compares their behaviour with the normal weight concrete slabs. In this respect, eight composite beams with channel shear connectors were tested in four-point bending to study the effects of concrete type, slab width, steel section, the spacing of shear connectors and beam span on the behaviour of the composite beams. It was observed that lightweight concrete can effectively be used in lieu of normal weight concrete, which reduces the concrete slab weight by 22% with a marginal reduction in both yielding and ultimate load capacities of the composite beams. The findings of this study have shown that effective slab width for ultimate limit state calculations should be different from that used for serviceability limit states. It was also found that the size of the steel beam expressed by its slenderness ratio (L/rs ) affects the value of the effective slab width. Steel beams with small slenderness ratios utilize wider portions of concrete slabs. Moreover, using LWC allows a considerable reduction in the number of required shear connectors without affecting the stiffness of the composite beams. Finally, design equations are proposed to accurately calculate the effective concrete width and the expected slip at the interface between concrete and steel in composite beams.